Evaluation of local damping effect on static and dynamic behaviors of granular materials using DEM modeling - N. Mahbubi Motlagh; A. Mahboubi; A. Noorzad (مهندسی عمران شریف, 2022)
Frictional sliding may not be sufficient for the stability of a system. In almost all models in the Discrete Element Method (DEM), a local non-viscous damping is used to balance the system by applying a damping force with a magnitude proportional to the unbalanced forces to each particle. The predicted macroscopic behavior of simulated particle assembly is influenced by the damping coefficient (α). In the present research, after calibrating the DEM simulations with the results of static and cyclic triaxial tests performed on sand samples containing rounded and angular particles under confining pressure of 100 kPa and cyclic stress ratio of 0.5, to study the effect of local non-viscous damping on the static and dynamic behavior of sands, different values of damping coefficient (0.5, 0.6, 0.7, 0.8 and 0.9) were used in simulations (in three-dimensional conditions). Then, the effects of initial void ratio, confining pressure, and particle shape on the behavior of the simulated samples were determined. The simulation results of the samples under static triaxial tests indicate that the effect of local non-viscous damping on the quasi-static behavior of granular materials is not significant. Under the same conditions, the energy stored in the samples with different damping coefficients is approximately equal. Angular specimens have a higher stored energy level. α has no significant effect on the coordinate number, magnitude of contact forces, and the maximum deformation in samples at the end of the static triaxial tests (20% axial strain). Upon increasing the damping coefficient from 0.5 to 0.9, the maximum rotational and translational velocities of both groups of samples are reduced. The higher the value of α considered in the simulation of cyclic triaxial test, the greater the dissipated energy of sample; thus, its damping ratio increases. By increasing the α coefficient, the shear modulus of round and angular particles decreases. The damping coefficient does not have a significant effect on the number of contacts between particles in the samples under cyclic triaxial tests, but the magnitude of contact forces, maximum rotational and translational velocities of the particles, and maximum deformation occurred in samples decreased with damping coefficient.